2013
DOI: 10.1302/2046-3758.22.2000137
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of performing a randomised controlled trial for femoroacetabular impingement surgery

Abstract: ObjectivesThe number of surgical procedures performed each year to treat femoroacetabular impingement (FAI) continues to rise. Although there is evidence that surgery can improve symptoms in the short-term, there is no evidence that it slows the development of osteoarthritis (OA). We performed a feasibility study to determine whether patient and surgeon opinion was permissive for a Randomised Controlled Trial (RCT) comparing operative with non-operative treatment for FAI.MethodsSurgeon opinion was obtained usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Indeed, equipoise is present within surgeon and patient communities for the arthroscopic treatment of FAI. 19 Results from robust clinical trials will inform decision makers and may give rise to more standardised care. Our forecast rise in the number of arthroscopic hip procedures of 1388% between 2002 and 2023 will accentuate challenging funding decisions within the NHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, equipoise is present within surgeon and patient communities for the arthroscopic treatment of FAI. 19 Results from robust clinical trials will inform decision makers and may give rise to more standardised care. Our forecast rise in the number of arthroscopic hip procedures of 1388% between 2002 and 2023 will accentuate challenging funding decisions within the NHS.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly salient given the increasing questions raised over the efficacy of arthroscopic knee surgery. 18 Randomised controlled trials are required to compare the efficacy of arthroscopic hip surgery with non-operative interventions, 19 and such studies are currently recruiting patients. 20 The adoption of hip arthroscopy in the UK has not been described.…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…It is also, therefore, too soon to conclude whether progression of OA is delayed with surgical correction 16 54 84 123. Experienced hip surgeons asserting that the link between morphology and OA of the hip has been established suggest that “not infrequently, we have come across patients with cam morphology who stand the test of time with minimal or no symptoms”109 and that “a large number of cam lesions are being excised unnecessarily.”124 RCTs comparing surgical and non-surgical management of FAI (and potential future OA development) are suggested as a future research priority 125…”
Section: Treatment Of Fai—more Questions Than Answersmentioning
confidence: 99%
“…There is uncertainty as to how symptomatic FAI is best treated 8 and the principal two management options are physiotherapy with activity modification or surgery. Both modalities have been shown to improve symptoms in the short term, 9 - 14 however, no published studies compare efficacy with each other or with sham procedures.…”
Section: Introductionmentioning
confidence: 99%
“…These two treatment modalities were chosen as comparators in a randomised controlled trial (RCT) after our feasibility study demonstrated equipoise amongst clinicians specialising in the field. 8 The feasibility study results have guided study design and the protocol was drafted in accordance with the SPIRIT 2013 Statement. 15 …”
Section: Introductionmentioning
confidence: 99%